Transition in spacetime - Korany, Mostafa Mohamed (JOURNAL OF ADVANCES IN PHYSICS, 2014)
The universe has two main dimensions spatial dimension (consists of three dimensions directional X, Y, Z) and the other dimension is the temporal dimension. Time and space are linked strongly inseparable so we will consider the time and place one Is the dimension of spacetime (as proved Einstein in his theory of relativity). Spacetime dimension includes the temporal dimension and spatial dimension (the three dimensions of space). Spacetime dimension two (real spacetime Vision spacetime). Spacetime has two cases: 1- Navigate spacetime 2- The change in spacetime. spacetime is Personally like a fingerprint and it always variable ( everyone has Personally spacetime and there are not find two of spacetime are the same.